2001
DOI: 10.1038/35102526
|View full text |Cite
|
Sign up to set email alerts
|

Sharper images by focusing soft X-rays with photon sieves

Abstract: Fresnel zone plates consisting of alternating transmissive and opaque circular rings can be used to focus X-rays. The spatial resolution that can be achieved with these devices is of the order of the width of the outermost zone and is therefore limited by the smallest structure (20-40 nm) that can be fabricated by lithography today. Here we show that a large number of pinholes distributed appropriately over the Fresnel zones make it possible to focus soft X-rays to spot sizes smaller than the diameter of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
222
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(228 citation statements)
references
References 8 publications
(3 reference statements)
5
222
0
1
Order By: Relevance
“…Many types of plasmonic lenses appeared subsequently such as metallic cone-shaped waveguide [1,2], width modulation-based lenses [3][4][5], elliptical nanopinhole lens [6,7], single circular ring-based lens [8][9][10][11], circular pinholes lens [12], nanowaveguide focusing [13], radial polarization-based circular grating lens [14,15], photon sieve [16], and polarization-based elliptical nanohole arrays [17,18]. All of the reported structures have functions and advantages of focusing surface plasmons, superfocusing within the range of micron-scale along propagation direction and spatial resolution beyond diffraction limit, and extraordinary transmission.…”
Section: Issn 1664-171xmentioning
confidence: 99%
“…Many types of plasmonic lenses appeared subsequently such as metallic cone-shaped waveguide [1,2], width modulation-based lenses [3][4][5], elliptical nanopinhole lens [6,7], single circular ring-based lens [8][9][10][11], circular pinholes lens [12], nanowaveguide focusing [13], radial polarization-based circular grating lens [14,15], photon sieve [16], and polarization-based elliptical nanohole arrays [17,18]. All of the reported structures have functions and advantages of focusing surface plasmons, superfocusing within the range of micron-scale along propagation direction and spatial resolution beyond diffraction limit, and extraordinary transmission.…”
Section: Issn 1664-171xmentioning
confidence: 99%
“…Menon et al showed the feasibility of ZPAL operating at a wavelength of 400nm and its potential for the fabrication of novel devices. Photon sieve is a novel diffractive optical element which consists of a great number of pinholes distributed appropriately over the Fresnel zones for the focusing and imaging of soft X-rays (Kipp et al, 2001). Photon sieve has advantages of the diameter of pinholes beyond the limitation of the corresponding Fresnel zone width and the minimum background in the focal plane, which is shown in figu re 3.…”
Section: Photon Sieve Array X-ray Maskless Nanolithographymentioning
confidence: 99%
“…Recently, another diffracting focusing element, the atom sieve, was introduced [19]. The atom sieve is based on the photon sieve invented earlier [20]. It consists of pinholes of varying size arranged across the Fresnel zones in such a manner that it is possible to focus on a spot with a diameter smaller than the smallest pinhole.…”
Section: Introductionmentioning
confidence: 99%